The presence of Turnip yellows virus in oilseed rape (Brassica napus L.) in Serbia - Milošević, Dragana N; Ignjatov, Maja; Nikolic, Zorica; Stankovic, Ivana; Bulajic, Aleksandra; Marjanovic-Jeromela, Ana; Krstic, Branka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
A total of 86 oilseed rape samples from six crops in different localities were collectedduring 2014 and analyzed for the presence of Turnip yellows virus (TuYV), Cauliflower mosaic virus (CaMV) and Turnip mosaic virus (TuMV) using commercial double-antibody sandwich (DAS)-ELISA kits. TuYV was serologically detected in 60 collected samples (69.77%), and none of the samples tested were positive for CaMV and TuMV. Six selected TuYV isolates were successfully transmitted by Myzus persicae to three test plants, confirming the infectious nature of the disease. In the selected ELISA-positive samples, the presence of TuYV was further confirmed by RT-PCR and sequencing. A comparison of the obtained sequence with those available in GenBank confirmed the presence of TuYV in oilseed rape samples. An analysis of P0 gene sequence data for a subset of these isolates showed they clustered with the known TuYV and were distinct from Beet western yellows virus (BWYV) isolates.
Keywords: Oilseed rape; Turnip yellows virus; Molecular detection; Serbia